Establishing a colorectal cancer research database from routinely collected health data: the process and potential from a pilot study. Issue 1 (23rd June 2022) - Tamm, Andres; Jones, Helen JS; Perry, William; Campbell, Des; Carten, Rachel; Davies, Jim; Galdikas, Algirdas; English, Louise; Garbett, Alex; Glampson, Ben; Harris, Steve; Khan, Khurum; et al.
Abstract : Objective: Colorectal cancer is a common cause of death and morbidity. A significant amount of data are routinely collected during patient treatment, but they are not generally available for research. The National Institute for Health Research Health Informatics Collaborative in the UK is developing infrastructure to enable routinely collected data to be used for collaborative, cross-centre research. This paper presents an overview of the process for collating colorectal cancer data and explores the potential of using this data source. Methods: Clinical data were collected from three pilot Trusts, standardised and collated. Not all data were collected in a readily extractable format for research. Natural language processing (NLP) was used to extract relevant information from pseudonymised imaging and histopathology reports. Combining data from many sources allowed reconstruction of longitudinal histories for each patient that could be presented graphically. Results: Three pilot Trusts submitted data, covering 12 903 patients with a diagnosis of colorectal cancer since 2012, with NLP implemented for 4150 patients. Timelines showing individual patient longitudinal history can be grouped into common treatment patterns, visually presenting clusters and outliers for analysis. Difficulties and gaps in data sources have been identified and addressed. Discussion: Algorithms for analysing routinely collected data from a wide range of sites and sources have been developed and refined to provide a rich data set that will be used to better understand the natural history, treatment variation and optimal management of colorectal cancer. Conclusion: The data set has great potential to facilitate research into colorectal cancer.